A Content Analysis of TV Series/Shows Watched by The Secondary and High School Students in Turkey - Alev Üstündağ; Özcan Doğan (Journal of Economy Culture and Society)
This study aimed to review TV series/shows’ content watched by teenagers in Turkey. The content of ten television shows with the highest ratings and popularity among teenagers between 10-14 and 15-18 were examined in terms of physical development (psychomotor and sexual development), cognitive/perceptual development, social/emotional development, language development, and other developmental issues such as violence, consumer culture, role modeling, family structure, and values. It was a descriptive study employing the content analysis method. The study data were collected using a “Content Evaluation Form for Children Shows." The findings revealed that TV shows mainly affected social and emotional development areas. They also reflected issues surrounding violence, cognitive/perceptual development, and role modeling. However, the influence of those shows on physical development was not significant.